AFFILIATED CHAIR OF TEACHER TRAINING COLLEGE: THE PRACTICAL EXPERIENCE - Marina Yu. Kulebyakina; Svetlana N. Gorshenina (Высшее образование в России)
The article addresses the topical aspects of activities of affiliated chairs of pedagogical higher education institution in the conditions of network interaction of the educational organizations. The authors consider the role of affiliated chairs in improvement the quality of vocational teacher's training in connection with introduction into the national education system of new federal state educational standards and the professional standard. Attention is focused on the main activities of the affiliated chairs of teacher college in the framework of a regional educational cluster: updating of the content of professional training programmes according to the requirements of the labor market, coordination of educational, methodical, and research activities of the educational organizations of the higher and general education, strengthening of a practical orientation in pedagogical personnel preparation, scientific and methodical support of life-long pedagogical education, assistance in graduates' professional adaptation and employment.